Research progress on innovative processing technologies and changes in physicochemical properties during the pickling of Pidan - CHENG Jing; LI Lichan; WANG Shaoyun; YU Liyang; YU Jie; CAI Xixi (Shipin yu jixie, 2023)
In view of the limitations of the traditional processing technology of Pidan, this review summarizes the innovative processing technologies of Pidan, such as gradient temperature control, ultrasonic assisted, vacuum decompression, pulsating pressure, etc., and describes the changes of water, pH value, protein, free amino acids, texture, mineral elements and micro-morphology during the picking process of Pidan. Moreover, the development directions of Pidan products are prospected.